The Role of Bales Nae Tradition in Strengthening Family Harmony and Social Cohesion in the Sasak Community of Lombok, Indonesia - Yazid, Afthon; Sugitanata, Arif; Hasan, Faradila; Ulirrahmi, Fauzia; Sholikhah, Siti Khamidatus (IAIN Manado, 2024)
This research investigates the